EPAS1 gain-of-function mutation contributes to high altitude adaptation in Tibetan horses - Xuexue Liu; Yanli Zhang; Yefang Li; Jianfei Pan; Dandan Wang; Weihuang Chen; Zhuqing Zheng; Xiaohong He; Qianjun Zhao; Yabin Pu; Weijun Guan; Han Jianlin; et al. (Oxford University Press, 2019)
High altitude represents some of the most extreme environments worldwide. The genetic changes underlying adaptation to such environments have been recently identified in multiple animals but remain unknown in horses. Here, we sequence the complete genome of 138 domestic horses encompassing a whole altitudinal range across China to uncover the genetic basis for adaptation to high-altitude hypoxia. Our genome data set includes 65 lowland animals across ten Chinese native breeds, 61 horses living at least 3,300 m above sea level across seven locations along Qinghai-Tibetan Plateau, as well as 7 Thoroughbred and 5 Przewalski’s horses added for comparison. We find that Tibetan horses do not descend from Przewalski’s horses but were most likely introduced from a distinct horse lineage, following the emergence of pastoral nomadism in Northwestern China ∼3,700 years ago. We identify that the endothelial PAS domain protein 1 gene (EPAS1, also HIF2A) shows the strongest signature for positive selection in the Tibetan horse genome. Two missense mutations at this locus appear strongly associated with blood physiological parameters facilitating blood circulation as well as oxygen transportation and consumption in hypoxic conditions. Functional validation through protein mutagenesis shows that these mutations increase EPAS1 stability and its hetero dimerization affinity to ARNT (HIF1B). Our study demonstrates that missense mutations in the EPAS1 gene provided key evolutionary molecular adaptation to Tibetan horses living in high-altitude hypoxic environments. It reveals possible targets for genomic selection programs aimed at increasing hypoxia tolerance in livestock and provides a textbook example of evolutionary convergence across independent mammal lineages.